Genesis and content of fitness: theoretical and methodological analysis - Evhen Prystupa; Liubov Chekhovska; Olha Zhdanova; Maryana Chekhovska (Jan Długosz University in Częstochowa, 2019)
Problem Statement. Becoming widespread and extremely popular with people throughout the world fitness has not left Ukraine, where there is a keen interest to this kind of recreational activities, aside. The Purpose was to study the origin of recreational fitness. Results: The article highlights the origins and genesis of health-related fitness in its international context, as well as in individual countries of the world. Particular attention has been paid to the development of recreational fitness in Ukraine and to the establishment of the Ukrainian market of fitness services, which originated in the late 90s. A rapid booming of fitness industry has been observed in Ukraine since 2005. The authors also deal with contemporary development of fitness services. At the same time the issue of terminological application has been tackled. Various publications put different interpretations fitness terminological system in general and of the term "fitness" as well. Although fitness as a health-improving system has been gradually evolving, the commonly accepted meaning of the term has not been elaborated up till now. Various definitions of the term should be considered as complementary. Conclusions. Fitness has a long history and different versions of origin and evolution. Two of them are considered to be of significance, i.e. the western and the eastern versions. For ideological reasons, fitness in the Soviet Union(Ukraine being part of it until1991)was practically ignored. Nevertheless, the mid-80s of the last century witnessed the breakthrough of fitness into the USSR. Establishment of the market of fitness services in the independent Ukraine started in the late 90s. Fitness industry in Ukraine ispermanently growing.